THE USE OF NON - VERBAL COMMUNICATION IN THE TEACHING OF ENGLISH LANGUAGE - AKINOLA, Oladipupo Abdullahi (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This paper attempted to investigate the use of various forms of non- verbal cues that are relevant to language teaching. It also examined its benefit to language education. Qualitative and quantitative research methods That is, survey research design and focus discussion group methods were adopted. The total number of 210 Copies of questionnaires was administered on the students while 23 different copies of questionnaires was also administered on the teachers apart from a ten member focus group discussion organized to elicit information about their experiences in the use of non verbal communication. Findings showed that though the teachers were awarded of the benefit of non verbal communication to language teaching, they do not have access to those non-verbal instructional materials that are most essential. This is therefore having negative effect on the academic performance of the students. Finally, the paper offers some recommendations on the availability and how the knowledge of non-verbal communication will improve the academic achievements of English language learners as well as making the task of impacting knowledge an easy one for the teachers also.